Activation of PKCα participates in the reduction of Ikur in atrial myocytes induced by tumour necrosis factor‐α. (9th October 2020) - Zhou, Hui‐shan; Peng, De‐wei; Lai, Ying‐yu; Li, Qian; Zhao, Jun‐fei; Deng, Chun‐yu; Yang, Hui; Li, Teng; Wang, Zhao‐yu; Xu, Yu‐wen; Xue, Yu‐mei; Wu, Shu‐lin; et al.
Abstract: The atrial‐specific ultra‐rapid delayed rectifier K + current (Ikur) plays an important role in the progression of atrial fibrillation (AF). Because inflammation is known to lead to the onset of AF, we aimed to investigate whether tumour necrosis factor‐α (TNF‐α) played a role in regulating Ikur and the potential signalling pathways involved. Whole‐cell patch‐clamp and biochemical assays were used to study the regulation and expression of Ikur in myocytes and in tissues from left atrial appendages (LAAs) obtained from patients with sinus rhythm (SR) or AF, as well as in rat cardiomyocytes (H9c2 cells) and mouse atrial myocytes (HL‐1 cells). Ikur current density was markedly reduced in atrial myocytes from AF patients compared with SR controls. Reduction of Kv1.5 protein levels was accompanied by increased expression of TNF‐α and protein kinase C (PKC)α activation in AF patients. Treatment with TNF‐α dose‐dependently reduced Ikur and protein expression of Kv1.5 but not Kv3.1b in H9c2 cells and HL‐1 cells. TNF‐α also increased activity of PKCα. Specific PKCα inhibitor Gö6976 alleviated the reduction in Ikur induced by TNF‐α, but not the reduction in Kv1.5 protein. TNF‐α was involved in the electrical remodelling associated with AF, probably by depressing Ikur in atrial myocytes via activation of PKCα. Abstract : The inflammatory factor TNF‐α might regulate Ikur by activating PKCα signaling pathways, leading to electrical remodeling of atrial myocytes and the occurrence of AF.